Technology and practice of passwords : International Conference on Passwords, PASSWORDS'14, Trondheim, Norway, December 8-10, 2014, revised selected papers /: International Conference on Passwords, PASSWORDS'14, Trondheim, Norway, December 8-10, 2014, revised selected papers. (2015) - Unknown
No abstract available